Specific stereoisomeric conformations determine the drug potency of cladosporin scaffold against malarial parasite - Das, Pronay; Babbar, Palak; Malhotra, Nipun; Sharma, Manmohan; Jachak, Goraknath R.; Gonnade, Rajesh G.; Shanmugam, Dhanasekaran; Harlos, Karl; Yogavel, Manickam; Sharma, Amit; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2018)
The dependence of drug potency on diastereomeric configurations is a key facet. Using a novel general divergent synthetic route for a three-chiral center antimalarial natural product cladosporin, we built its complete library of stereoisomers (cladologs) and assessed their inhibitory potential using parasite-, enzyme-, and structure-based assays. We show that potency is manifest via tetrahyropyran ring conformations that are housed in the ribose binding pocket of parasite lysyl tRNA synthetase (KRS). Strikingly, drug potency between top and worst enantiomers varied 500-fold, and structures of KRS-cladolog complexes reveal that alterations at C3 and C10 are detrimental to drug potency whereas changes at C3 are sensed by rotameric flipping of glutamate 332. Given that scores of antimalarial and anti-infective drugs contain chiral centers, this work provides a new foundation for focusing on inhibitor stereochemistry as a facet of antimicrobial drug development.

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin

Synthesis and biological evaluation of hoshionolactam-based compounds - Jachak, Gorakhnath R.; Elizebath, Drishya; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
In search of novel antitrypanosomal agents based on hoshinolactam (IC50=3.9 nM), we disclose the synthesis and biological evaluations of 14 different analogues of the natural product using combinations of different acids and lactams. Antitrypanosomal activity assays revealed that the synthesized analogues were less potent than the parent natural product.
Keywords: Hoshinolactam; Ozonolysis; Parasitic diseases; Trypanosoma